2017
DOI: 10.18632/oncotarget.16802
|View full text |Cite
|
Sign up to set email alerts
|

miR-509-3-5P inhibits the invasion and lymphatic metastasis by targeting PODXL and serves as a novel prognostic indicator for gastric cancer

Abstract: BackgroundOur study aimed to investigate the clinicopathological feature and prognostic role of miR-509-3-5P in gastric cancer, to determine the invasive and metastatic role of miR-509-3-5P in vitro and in vivo and to explore the molecular mechanism between miR-509-3-5P and PODXL.ResultsStrikingly lower miR-509-3-5P expression was detected in gastric cancer tissues with advanced tumor stage, poor differentiation and advanced pT stage, and was regarded as an independent prognostic role for poor prognosis. MiR-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Here, we used the IHC method to detect PODXL expression in GC tissues and their corresponding NAT. A similar analysis performed by others also indicated that PODXL was a target gene of miR‐509‐3‐5p in GC patients and mediated tumor progression . Interestingly, our results also showed that PODXL was expressed more frequently in GC tissues compared with NAT.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Here, we used the IHC method to detect PODXL expression in GC tissues and their corresponding NAT. A similar analysis performed by others also indicated that PODXL was a target gene of miR‐509‐3‐5p in GC patients and mediated tumor progression . Interestingly, our results also showed that PODXL was expressed more frequently in GC tissues compared with NAT.…”
Section: Discussionsupporting
confidence: 89%
“…A similar analysis performed by others also indicated that PODXL was a target gene of miR-509-3-5p in GC patients and mediated tumor progression. 24 Interestingly, our results also showed that PODXL was expressed more frequently in GC tis- Recent studies on the genomic landscape of gastric adenocarcinoma have identified several key signaling molecules, including epidermal growth factor receptor family (ErbB) members, vascular endothelial growth factor (VEGFR) receptor family members, and PI3K/Akt, NF-κB and MAPK/ERK pathway components, that were implicated in the molecular pathogenesis of GC. 37 For example, PI3Kp85α and p-AKT were expressed in gastric adenocarcinoma tissues, and targeting blockade of the PI3K pathway might inhibit GC growth and metastasis through downregulation of Ki-67 and MMP-2 expression.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…These inconsistent results may be due to the different tumor types or microenvironments such as in vitro and in vivo . miRNA‐509‐3 has been previously identified as a tumor suppressor gene in lung cancer , ovarian cancer , hepatoma , leukemia , renal cell carcinoma , and GC . It was also an independent prognostic biomarker in GC patients.…”
Section: Discussionmentioning
confidence: 99%